Conformational distortion of α-phenylethyl amine in cryogenic matrices – a matrix isolation VCD study. Issue 19 (29th April 2016) - Pollok, Corina H.; Merten, Christian
Abstract : MI-VCD spectroscopy reveals conformational perturbations of a chiral amine due to matrix packing effects. Abstract : The chiral amine α-phenylethyl amine (PEA) was isolated in cryogenic matrices and investigated using vibrational circular dichroism (VCD) and infrared spectroscopy. The potential energy surface (PES) of PEA features five different conformers connected by relatively low conformational transition states. Based on the IR spectra, it could be confirmed that all conformational energy barriers are passed at a deposition temperature of 20 K, and that only the global minimum conformation of PEA is populated in both argon and nitrogen matrices. However, differences in the calculated and experimental VCD spectra indicate deviations from the minimum structure by perturbation of the phenyl ring as well as of the amine orientation. The degree of the perturbation is found to also depend on the choice of the host gas, which shows the subtle influence of the environment on the conformational distortion of PEA.